1987
DOI: 10.1007/bf00215437
|View full text |Cite
|
Sign up to set email alerts
|

In vivo binding and uptake of low-density lipoprotein-gold- and albumin-gold conjugates by parenchymal and sinusoidal cells of the fetal rat liver

Abstract: To elucidate the participation of fetal rat liver cells in the receptor-mediated internalization of low-density lipoproteins (LDL), rat fetuses were injected with either LDL-gold or albumin-gold conjugates. The degree of binding and uptake of LDL-gold and albumin-gold by parenchymal and sinusoidal cells of the fetal rat liver differs markedly. Endothelial cells exhibit low LDL-gold uptake. In contrast, parenchymal cells internalize LDL-gold more actively (45 +/- 8 LDL conjugates/100 micrometers2 cytoplasm with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Thus, in sepa rate experiments it could be shown that estro gen significantly decreased the serum LDL apoB concentration from day 30 after birth. The presence of estrogen receptors in fetal 233 rodents has been repeatedly documented [24][25][26], In connection with our own studies it seems to be of interest that the transcription mechanism responds to estrogen in various tissues also during fetal development [26], In a morphological study with gold-labeled LDL Franke et al [3] found a stimulation of LDL uptake into the fetal liver by estrogen. In in vivo experiments the uptake of gold-labeled LDL into either liver parenchymal cells or Kupffer's cells was increased 2-fold.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, in sepa rate experiments it could be shown that estro gen significantly decreased the serum LDL apoB concentration from day 30 after birth. The presence of estrogen receptors in fetal 233 rodents has been repeatedly documented [24][25][26], In connection with our own studies it seems to be of interest that the transcription mechanism responds to estrogen in various tissues also during fetal development [26], In a morphological study with gold-labeled LDL Franke et al [3] found a stimulation of LDL uptake into the fetal liver by estrogen. In in vivo experiments the uptake of gold-labeled LDL into either liver parenchymal cells or Kupffer's cells was increased 2-fold.…”
Section: Discussionmentioning
confidence: 90%
“…In summary, the LDL catabolism of the rat is insensitive towards estrogen in the late gestational period and during the first 2 weeks of postnatal life [3], The efflux of the atherogenic LDL from the blood stream is mainly mediated via spe cific receptors. Elimination occurs for the ma jor part in the liver, which is a key organ in the regulation of the plasma LDL concentration in certain species including man [1], The he patic LDL receptor was found to be expressed in rats [2][3][4], cattle [5], pigs [6] and humans [7] also in the fetal state, and a high negative correlation was found between the fetal plasma cholesterol and the LDL receptor con centration [5][6][7]. The expression of the heDr.…”
mentioning
confidence: 99%
“…Albumin enters the cell via a caveolae-dependent endocytosis pathway (Franke et al, 1987;Schubert et al, 2001). R-MT was mixed with F-albumin, and the uptake of the protein mixture was imaged in a single cell (Fig.…”
Section: Cellular Uptake Of Mt By Endocytosismentioning
confidence: 99%
“…Colloidal gold particles of different sizes can be easily produced (24,50,54) and macromolecules such as enzymes, antibodies, lipoproteins, and hormones can be directly adsorbed on their surfaces (10,15,22,28) without modification of their biochemical and physiological properties (18,42,44,47,49,55). The one known exception 387 388 CATHIENI, TABAN is catalase (27).…”
Section: -401 1992)mentioning
confidence: 99%
“…With immunostaining techniques, visualization of the binding site-antibody complex is presently carried out by using a second FITC-or RITC-labeled antibody or with the use of peroxidase, ferritin or, more recently, colloidal gold (5,17,45,50,63). When used, colloidal gold particles can be further enhanced by the application of a photographic silver emulsion (11,12,14,41,52).Colloidal gold particles of different sizes can be easily produced (24,50,54) and macromolecules such as enzymes, antibodies, lipoproteins, and hormones can be directly adsorbed on their surfaces (10,15,22,28) without modification of their biochemical and physiological properties (18,42,44,47,49,55). The one known exception 387 388 CATHIENI, TABAN is catalase (27).…”
mentioning
confidence: 99%